Retrospective analysis of the prevalence of and factors associated with condom use among young HIV-infected women in Cameroon. (14th January 2016) - Pilapil, Mariecel; Morris, Lee; Saito, Kohta; Kouya, Francine; Maku, Vivian; Kwalar, Rene; Palmer, Nancy; Tih, Pius Muffih; Jao, Jennifer
Objectives: Young women are more likely to be infected with HIV globally, in sub-Saharan Africa, and in Cameroon. Despite its clear clinical and public health benefits, condom use among HIV-infected women continues to be low. The objective of this study was to describe the prevalence of inconsistent condom use among HIV-infected women in Cameroon and the factors associated with it. Methods: We conducted a cross-sectional study of HIV-infected young women aged 17–26 years from three semi-urban HIV clinics in the Northwest Region of Cameroon. This study was a subgroup analysis of a previously reported study on inconsistent condom use in HIV-infected and -uninfected youth. Inconsistent condom use was defined as reporting "sometimes" or "never" to questions regarding frequency of condom use. Logistic regression modeling was used to determine factors associated with inconsistent condom use. Results: A total of 84 participants were recruited and submitted completed questionnaires for analysis. Median age was 24 years (interquartile range = 22–25) and the median age at HIV diagnosis was 21 years (interquartile range = 20–23). Fifty percent of the participants reported no prior schooling or only primary school education. Overall, 61/84 (73%) reported inconsistent condom use. After adjusting for potential confounders, education to the secondary school level was protective against inconsistent condom use (odds ratio = 0.19; confidence interval: 0.04–0.95), and having ≥2 pregnancies was associated with inconsistent condom use (odds ratio = 7.52; confidence interval: 1.67–34.00). Conclusion: There is a high prevalence of inconsistent condom use among young HIV-infected women in Cameroon, which appears to be associated with lower levels of educational attainment and higher parity. Further larger studies assessing the factors associated with poor condom use in this population are warranted and may inform public health policy in resource-limited settings with high HIV prevalence.